2012
DOI: 10.1371/journal.pone.0036292
|View full text |Cite
|
Sign up to set email alerts
|

Activation of an NLRP3 Inflammasome Restricts Mycobacterium kansasii Infection

Abstract: Mycobacterium kansasii has emerged as an important nontuberculous mycobacterium pathogen, whose incidence and prevalence have been increasing in the last decade. M. kansasii can cause pulmonary tuberculosis clinically and radiographically indistinguishable from that caused by Mycobacterium tuberculosis infection. Unlike the widely-studied M. tuberculosis, little is known about the innate immune response against M. kansasii infection. Although inflammasome activation plays an important role in host defense agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 109 publications
(105 reference statements)
5
57
0
1
Order By: Relevance
“…In addition, the experiments performed using cytochalasin indicated that the internalization of the parasite by macrophages is required for inflammasome activation. Collectively, the data demonstrate that the invasion of viable trypomastigotes is essential for triggering caspase-1 activation, which is consistent with other studies showing that the invasion of the macrophages with viable pathogens is necessary to stimulate the caspase-1 pathway (38,39). We speculate that the parasite escape from the vacuole to the cytoplasm is pivotal for inducing lysosomal damage and consequently the NLRP3-dependent activation of the inflammasome.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the experiments performed using cytochalasin indicated that the internalization of the parasite by macrophages is required for inflammasome activation. Collectively, the data demonstrate that the invasion of viable trypomastigotes is essential for triggering caspase-1 activation, which is consistent with other studies showing that the invasion of the macrophages with viable pathogens is necessary to stimulate the caspase-1 pathway (38,39). We speculate that the parasite escape from the vacuole to the cytoplasm is pivotal for inducing lysosomal damage and consequently the NLRP3-dependent activation of the inflammasome.…”
Section: Discussionsupporting
confidence: 91%
“…2). It should be noted that the characterization of these cells, including quantification of reduced expression levels relative to those in nontarget control cells, was previously reported (see Materials and Methods) (29)(30)(31)(32). Cdt induced a dose-dependent release of both IL-1␤ and IL-18 in macrophages derived from both wild-type and shRNA control (shCtl) THP-1 cells ( Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Preparation of THP-1 cells stably expressing short hairpin RNA (shRNA) against caspase-1 (shCasp1), NLRP3 (shNLRP3), and ASC (shASC) as well as nontarget controls was previously described (29)(30)(31); these cells have been well characterized, and expression levels were quantified to be reduced Ͼ75% for shNLRP3, Ͼ95% for shASC, and Ͼ90% for shCasp1 cells, with no effect on the nontarget controls (32). THP-1 cells were differentiated into macrophages by incubating cells in the presence of 50 ng/ml phorbol myristate acetate (PMA) for 48 h, at which time the cells were washed and incubated an additional 24 h in medium prior to use.…”
Section: Cellsmentioning
confidence: 99%
“…Ceramide, another mediator of TNF-α function, has been reported to selectively inhibit complex III activity in isolated cardiac mitochondria [74]. Moreover, in adipocytes, the changes induced by TNFα cause pronounced morphological changes in the mitochondria, presumably due to variations in the levels of several mitofusion proteins [78].…”
Section: Tumor Necrosis Factor α (Tnf-α)mentioning
confidence: 99%